Dynamics of the Light Harvesting Complex network - (:unkn) unknown (My University, 2025)
Efficient use of the light is essential for the fitness of photosynthetic organisms. It is believed that the evolution of an antenna network system, capable of dynamic regulation of the fraction of light energy to be transferred to the photosystems and to dissipate light excess is a key step in the evolution of photosynthetic eukaryotes and a crucial step in land colonization. The core structure of the pigment-protein complexes devoted to light harvesting (LHCs) is largely conserved among eukaryotes. However, the regulatory portions display a certain degree of variability which may underlie their role in specific adaptation to particular climatic conditions. The aim of the proposed research project is to understand the network of interactions between the proteins of the thylakoid membrane that allows coping with the changes in light quality and regime exploiting the model organisms Arabidopsis thaliana. In particular, the project will focus on the contribution of the N-terminal domain of the major light harvesting antenna (LHCII) and its phosphorylation to the regulatory dynamics of the thylakoids. The primary focus will be to understand the contribution of the two major isoforms of the LHCII complex LHCB1 and LHCB2. These being the major components of the trimeric LHCII and dynamically phosphorylated at the N-terminus. At the end of the proposed project the specific role of each isoforms’ N-terminus in vivo for the regulation of photosynthetic electron transfer, the assembly of photosynthetic supercomplexes and the architecture of the thylakoid membrane network will be revealed. The key tool for the investigation will be the production of Arabidopsis lines expressing mutated versions of the major light harvesting complex isoforms. These will be obtained by complementing previously produced knock-out lines with LHCII isoforms containing a modified phosphorylation site. By analyzing their photosynthetic performance and photosystems structure under changing light regimes it will be possible to elucidate the role of their dynamic interaction with other components of the photosynthetic machinery. Furthermore, the results will allow the elaboration of hypotheses on the evolution of this regulation system. Moreover, since antenna re-organization is central in the photosynthetic acclimation responses, the new detailed knowledge should allow informed manipulations of its kinetics. It has already been demonstrated that by reducing the response time it is possible to engineer a higher productivity in the field. Furthermore, understanding these mechanisms will offer new targets for genetic selection in crop breeding programs and provide concepts applicable to the design of artificial-photosynthesis systems.
Keywords: Light Harvesting Complex Phosphoproteome Photosynthesis Arabidopsis thaliana Light Acclimation